The effect of breath-hold diving on selected adaptive mechanisms in the circulatory-respiratory system in simulated static and dynamic apnoea - MAGDALENA SOLICH-TALANDA; RAFAŁ MIKOŁAJCZYK; ROBERT ROCZNIOK; ALEKSANDRA ŻEBROWSKA (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2019)
Background: ‪Current research results indicate high adaptation of an organism to long-term apnoea. Breathing techniques allow increasing the volume of the inhaled air and thus prolong the breath-hold time at rest and during physical effort. The purpose of this study was to assess the impact of breath-hold on adaptations of the respiratory and circulatory systems and cardiopulmonary-respiratory reactions at rest and during physical effort in persons practising freediving. Material and methods: ‪The study involved 17 athletes practising breath-hold diving, at the mean age of 38.4 ±8.4 years. Spirometry tests to evaluate static and dynamic lung indicators were conducted. The heart rate (HR), oxygen saturation (SpO2), and the apnoea time in three breath-hold trials were measured: static dry STA-D, static with face immersed in water STA-I and dynamic (DYN-D). Results: ‪The values of spirometry indicators were higher than the normal values at the appropriate peak expiratory flow (91.6 ± 27.2%). A significant effect of breath-hold on the HR was demonstrated in the STA-D test (W = 0.43, at p < 0.05) and STA-I (W = 0.51, at p < 0.05). The mean breath-hold time was significantly lower in the dynamic trial DYN-D vs STA-D (p < 0.001) and in STA-D Ex vs STA-I (P < 0.001). Higher mean values of SpO2 were shown in DYN-D in comparison to STA-D (p < 0.05). Conclusions: ‪The results of this study indicate that breath-hold training beneficially affects adaptation of the circulatory system, causing strong bradycardia and lower tolerance in response to prolonged apnoea during physical effort.